2006
DOI: 10.1016/j.foreco.2006.05.057
|View full text |Cite
|
Sign up to set email alerts
|

Pasture, tree and soil evolution in silvopastoral systems of Atlantic Europe

Abstract: Increased forest area and wood production is a key goal for the European Union, together with avoidance of hazards that damage forests. Galicia is a region of northwest Spain that belongs to the Atlantic biogeographic region with very high wood production, but due to climate fire has a major negative impact on forest productivity (i.e. it represents 16% of the fires of Europe). Silvopastoral systems offer the potential to enhance forest productivity as well as to obtain income from newly afforested areas in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 11 publications
7
45
0
4
Order By: Relevance
“…Mineral fertilization in silvopastoral systems developed with Pinus radiata in initial neutral soils caused a significant reduction on tree growth. Rigueiro-Rodríguez et al (2000) and Mosquera-Losada (2006) observed that tree diameter and height were reduced by mineral fertilization compared with no fertilization or organic fertilization. This can be explained, first, because in fertile soils the soil pH did not limit pasture development and, therefore, the response of pasture production to mineral fertilization was positive, which enhances the competition between pasture and trees and reduces tree growth in the first development stages (initial tree height 20 cm).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Mineral fertilization in silvopastoral systems developed with Pinus radiata in initial neutral soils caused a significant reduction on tree growth. Rigueiro-Rodríguez et al (2000) and Mosquera-Losada (2006) observed that tree diameter and height were reduced by mineral fertilization compared with no fertilization or organic fertilization. This can be explained, first, because in fertile soils the soil pH did not limit pasture development and, therefore, the response of pasture production to mineral fertilization was positive, which enhances the competition between pasture and trees and reduces tree growth in the first development stages (initial tree height 20 cm).…”
Section: Discussionmentioning
confidence: 98%
“…Agenda 21 (UN 1992) describes silvopastoral systems as sustainable land management and as a way of increasing income from forestry in the short-and medium-terms (Mosquera-Losada et al 2006). Moreover, silvopastoral systems should be also implemented in Galicia as a way of reducing forest fires, one of the most important environmental problems in northern Spain, which contributes to 16% of the total annual area burnt in Europe (RigueiroRodríguez et al 2005b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Las sabanas naturales como ecosistemas donde coexiste la vegetación herbácea y la arbustiva y los grandes herbívoros también se han estudiado, en África (McNaughton 1979, Knoop y Waker 1985, Belsky et al 1989, Mordelet y Menaut 1995, Ong y Leakey 1999, Ludwig et al 2004, Sankaran et al 2005, Treydte et al 2007, Asner et al 2009) y en Norteamérica (McNaughton 1968, Belsky y Canham 1994, McPherson 1997, Jose et al 2004. En estas regiones y en otras más templadas también existen sistemas de uso ganadero que incorporan el arbolado (Cooper et al 1996, Feldhake 2001, Alavalapati et al 2004, Mosquera-Losada et al 2006, Guevara-Escobar et al 2007, Benavides et al 2009), con importantes beneficios para las características productivas de las comunidades herbáceas, la diversidad biológica y la provisión de servicios ambientales (Young 1989, Sanchez 1995, Etienne 1996, Altieri 1999, Jose et al 2004, Palma et al 2007, Benavides et al 2009, Jose 2009, Pastur et al 2012). …”
Section: Bases Ecológicas De Los Sistemas De Uso Silvopastoralunclassified
“…The developed model cannot be applied to all types of silvopastoral systems but only to those ones established by planting trees and sowing grass at the same time on abandoned agricultural lands (Mosquera-Losada et al 2006, Fernández-Núñez et al 2007. The model and the whole simulation-optimisation system can be improved with new information regarding the dynamics of the understory vegetation and the competition relationships among trees and bushes or herbaceous vegetation (Pollock et al 1994, Chang et al 2002, Peri et al 2002, Ares et al 2003 especially when both occupy the same strata (e.g., when tree plantations are young).…”
Section: Silvipastoral Systemsmentioning
confidence: 99%